2021 European Thyroid Association Guidelines for the Management of Iodine-Based Contrast Media-Induced Thyroid Dysfunction - Bednarczuk, Tomasz (Eur Thyroid J, 2021)
Given the fact that a large number of radiological examinations using iodine-based contrast media (ICM) are performed in everyday practice, clinicians should be aware of potential ICM-induced thyroid dysfunction (TD). ICM can induce hyperthyroidism (Hyper) or hypothyroidism (Hypo) due to supraphysiological concentrations of iodine in the contrast solution. The prevalence of ICM-induced TD varies from 1 to 15%. ICM-induced Hyper is predominantly found in regions with iodine deficiency and in patients with underlying nodular goiter or latent Graves' disease. Patients at risk for ICM-induced Hypo include those with autoimmune thyroiditis, living in areas with sufficient iodine supply. Most cases of ICM-induced TD are mild and transient. In the absence of prospective clinical trials on the management of ICM-induced TD, an individualized approach to prevention and treatment, based on patient's age, clinical symptoms, pre-existing thyroid diseases, coexisting morbidities and iodine intake must be advised. Treatment of ICM-induced Hyper with antithyroid drugs (in selected cases in combination with sodium perchlorate) should be considered in patients with severe or prolonged hyperthyroid symptoms or in older patients with underlying heart disease. It is debated whether preventive therapy with methimazole and/or perchlorate prior to ICM administration is justified. In ICM-induced overt Hypo, temporary levothyroxine may be considered in younger patients with symptoms of Hypo, with an underlying autoimmune thyroiditis and in women planning pregnancy. Additional clinical trials with clinically relevant endpoints are warranted to further aid in clinical decision-making in patients with ICM-induced TD.